Optimum Frequency Droop Control of Islanded Micro-Grid Using PID-PSO Controller - Shamshiri, Meysam; Gan, Chin Kim; Omar, Rosli; Ab Ghani, Mohd Ruddin (Praise Worthy Prize, 2014)
The voltage and frequency are two of the important parameters to ensure the safe operation of a micro-grid, particularly in the event of island operation. This paper presents a method to control the frequency of the synchronous generator in islanded micro-grid operation. The DC motor has been utilized as the prime mover of generator. The main objective of this paper is to control the DC motor speed rotation which will consequently control the output frequency. The PID controller has been used and the coefficients of PID controller have been tuned by Ziegler-Nichols (Z-N) and Particle Swarm Optimization (PSO)methods. This is to minimize the transient response of the DC motor speed control which are rise time, settling time and overshoot time. The results show the PID-PSO algorithm has better response in terms of settling and overshoot times as compared to the Z-N and Genetic Algorithm (GA) methods.